Co‐existent pilocytic astrocytoma with acute B‐cell leukemia within the cerebellum. Issue 5 (13th August 2019) - Hickman, Richard; Leeman‐Neill, Rebecca; Rosenblum, Marc; Anderson, Richard; Goldman, James
Abstract : Pilocytic astrocytomas are the commonest childhood brain tumor. They are typically benign and usually are solitary neoplasms. To our knowledge, only one report of a pilocytic astrocytoma with leukemia has been previously issued. We herein describe the first case with documented histopathology of a 2‐year‐old boy who had a cerebellar pilocytic astrocytoma co‐localized with an acute B‐lymphoblastic leukemia. We speculate that chemotactic migration of leukemic cells to the pilocytic astrocytoma may be partly mediated through vascular endothelial growth factor (VEGF) and VEGF receptors.